1997
DOI: 10.1007/s004420050158
|View full text |Cite
|
Sign up to set email alerts
|

Variations in leaf β 13 C along a vertical profile of irradiance in a temperate Japanese forest

Abstract: The vertical profile of stable carbon isotope ratios (δC) of leaves was analyzed for 13 tree species in a cool-temperate deciduous forest in Japan. The vertical distribution of long-term averaged δC in atmospheric CO (δ) was estimated from δC of dry matter from NADP-malic enzyme type C plant (Zea mays L. var. saccharata Sturt.) grown at a tower in the forest for 32␣days, assuming constant Δ value (3.3‰) in Z. mays against height. The δ value obtained from δC in Z.␣mays was lowest at the forest floor (-9.30 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
79
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 33 publications
12
79
0
Order By: Relevance
“…Although our data are similar to those on stable carbon isotope variations in single tree foliage obtained by other authors Long 1982, 1986;Hanba et al 1997;Schleser 1999), our results refer to segmented needles. The main objective of this study was to determine homogeneity of C isotope composition in single needles of pine trees.…”
Section: Introductionsupporting
confidence: 91%
“…Although our data are similar to those on stable carbon isotope variations in single tree foliage obtained by other authors Long 1982, 1986;Hanba et al 1997;Schleser 1999), our results refer to segmented needles. The main objective of this study was to determine homogeneity of C isotope composition in single needles of pine trees.…”
Section: Introductionsupporting
confidence: 91%
“…Indeed, various studies revealed an increase of d 13 C in tree biomass with increasing irradiance (e.g., Hanba et al 1997). The 1926-1975 and 1976-2005 in aggregated neighborhood categories (relative contribution of Fagus to competition index (CI) 70-100%: Fagus70-100, n = 9; relative contribution of Fagus to competition index CI \ 70%: Fagus\70, n = 7).…”
Section: Discussionmentioning
confidence: 99%
“…Aboveground competition may also result in changes of the canopy structure and the light regime, thereby affecting the d 13 C signature of leaf mass (Medina et al 1991;Buchmann et al 1997;Hanba et al 1997;West et al 2001). Further, competition could affect the water availability for the competing species in a mixed stand.…”
Section: Introductionmentioning
confidence: 99%
“…10.1 and 10.2), and some environmental variables was originally conceptualized in a seminal paper by Francey and Farquhar (1982). One important size-related environmental change is increased shading within tree crowns (Francey et al 1985;Ehleringer et al 1986;Hanba et al 1997;Carswell et al 2000;Parker et al 2002;Poorter et al 2005;Lloyd et al 2009) which raises p c because A declines via reduced light interception. This change in the light environment occurs within the height profile of individual trees within closed-canopy forests, but does not occur at the tops of canopy-dominant trees or in open-grown trees.…”
Section: Introductionmentioning
confidence: 99%
“…(10.1-10.3), D declined with decreasing p c due to increased A at higher irradiance, and decreased g c with longer branch lengths. Other structural and physiological responses to increased tree size that can impact D include increases in leaf thickness (Vitousek et al 1990;Bond et al 1999;Hanba et al 1997;Koch et al 2004;Ishii et al 2008;Ambrose et al 2009;Ishii 2011) and hence decreasing g i (Warren and Adams 2006), although correlations between g i and leaf thickness are not always observed (Terashima et al 2005). This morphological response is commonly thought to be adaptive to the light environment, although it also driven by the gravitational constraint on leaf water potential (0.01 MPa m −1 ) and subsequent impacts on turgor during leaf expansion (e.g.…”
Section: Introductionmentioning
confidence: 99%